Experiment based on orbit satellite and application for sparse microwave imaging - Jing TIAN; Li-hong KANG; Xi-long SUN; Zhou LI; Bing-chen ZHANG (Tongxin xuebao)
The experiment aiming to verify the sparse microwave image methodology based on orbit SAR satellite was presented.During the experiment,the imaging parameters were changed in order to achieve the uniform de-sampling echo data.The image quality evaluation method for sparse microwave imaging was proposed and quantified evaluation results for the experiment were also presented.Finally,the remote applications of sparse microwave imaging were prospected.